3x+2(x+1)=6x+(3x-4)

Simple and best practice solution for 3x+2(x+1)=6x+(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+2(x+1)=6x+(3x-4) equation:


Simplifying
3x + 2(x + 1) = 6x + (3x + -4)

Reorder the terms:
3x + 2(1 + x) = 6x + (3x + -4)
3x + (1 * 2 + x * 2) = 6x + (3x + -4)
3x + (2 + 2x) = 6x + (3x + -4)

Reorder the terms:
2 + 3x + 2x = 6x + (3x + -4)

Combine like terms: 3x + 2x = 5x
2 + 5x = 6x + (3x + -4)

Reorder the terms:
2 + 5x = 6x + (-4 + 3x)

Remove parenthesis around (-4 + 3x)
2 + 5x = 6x + -4 + 3x

Reorder the terms:
2 + 5x = -4 + 6x + 3x

Combine like terms: 6x + 3x = 9x
2 + 5x = -4 + 9x

Solving
2 + 5x = -4 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
2 + 5x + -9x = -4 + 9x + -9x

Combine like terms: 5x + -9x = -4x
2 + -4x = -4 + 9x + -9x

Combine like terms: 9x + -9x = 0
2 + -4x = -4 + 0
2 + -4x = -4

Add '-2' to each side of the equation.
2 + -2 + -4x = -4 + -2

Combine like terms: 2 + -2 = 0
0 + -4x = -4 + -2
-4x = -4 + -2

Combine like terms: -4 + -2 = -6
-4x = -6

Divide each side by '-4'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 7n-20=-48 | | c^2+14c+45= | | m^2+6m+4=-4 | | 4i(6+2i)= | | y=3.0x+1.7 | | 6x+3=12-2x | | t(5t+2)= | | 276/12 | | Y=6x^2+x-15 | | -(-21y+29)-21y=-(19y+23)+26 | | 4m+6m+7m= | | 81w^2-49= | | -(67r+8s+61)= | | 5(3-y)/3=y-5 | | X^2-13x-168= | | 2x-1=y+4 | | 16-5(3p-4)=8(-2p+11) | | 9=3(5q-2) | | -6x+3(3)= | | X+8=4(X-10) | | -4x-6=-42 | | x/2-5=6 | | (1/3)x=1017 | | 120+x^2-200+11x=100 | | 2x+2=3x-ray | | x^2-14x=-53 | | 120+x^2-200+11x=P | | -4x-6=22 | | 3(x-7)+2=12x-3 | | x^4=-81x^2 | | 12-8y=13 | | 6x=2(2x-3) |

Equations solver categories